Integration Face Recognition and Body Temperature - Christin Erniati Panjaitan; Dara Hagayna; David Prandi; Remancus Wiranto (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2021)
Commonly, absence is done manually on the prepared paper. This thing is less effective because wasting time and distract student's focus in the classroom. To solve that problem, this research is using Face Recognition. Face Recognition is a face detection technology. This technology is using Artificial Intelligence (AI) to indetify faces. Face Recognition also can reduce the way that student pretend present but in fact is not. This tecnology is better than convetional method. In application, camera is used to record and detect faces. We used Raspberry Pi 3b as a main part. Moreover, in this research, we integrate face recognition with temperature sensors and buzzer Testing in each component is on average successful and some fail. But it is in accordance with the rules of the system made.